Non-Problematic Risks from Low-Dose Radiation-Induced DNA Damage Clusters - Daniel P. Hayes (SAGE Publishing, 2008)
Radiation-induced DNA damage clusters have been proposed and are usually considered to pose the threat of serious biological damage. This has been attributed to DNA repair debilitation or cessation arising from the complexity of cluster damage. It will be shown here, contrary to both previous suggestions and perceived wisdom, that radiation induced damage clusters contribute to non-problematic risks in the low-dose, low-LET regime. The very complexity of cluster damage which inhibits and/or compromises DNA repair will ultimately be responsible for the elimination and/or diminution of precancerous and cancerous cells.